Representation of Remilitarization and Nationalism under Shinzo Abe’s Regime at ‘Kamen Rider Build Series’ - Hamdan Nafiatur Rosyida (Vocational College of Diponegoro University, 2023)
Through the television show Kamen Rider Build, Shinzo Abe, who was re-elected as prime minister of Japan for the term 2012–2020, attempted to reinterpret Article 9 of the Japanese Constitution. This study highlights the remilitarization and nationalism issue. This paragraph includes a demilitarization issue to do rid of the honor pacifist mentality that military troops adopted as a result of American pressure following Japan's humiliating defeat in World War II. Japan, which Abe ultimately labels an